Antihypertensive therapy in pre-eclampsia: Effects of plasma from nonresponsive patients on endothelial gene expression - Luizon, Marcelo R. [UNESP]; Caldeira-Dias, Mayara [UNESP]; Deffune, Elenice [UNESP]; Fernandes, Karla S.; Cavalli, Ricardo C.; Tanus-Santos, José E.; Sandrim, Valéria C. [UNESP] (Taylor & Francis, 2016)
Aim: Over 40% of patients with pre-eclampsia are nonresponsive to antihypertensive therapy, but the underlying mechanisms are unknown. We examined the effects of plasma from nonresponsive and responsive patients on endothelial gene expression. Patients & methods: PCR array was performed in human umbilical vein endothelial cells (HUVEC) incubated with plasma from nonresponsive (n = 4) and responsive (n = 4) patients. Gene networks and interactions with antihypertensive drugs used in pre-eclampsia were identified by Ingenuity Pathway Analysis. Results: Nifedipine and hydralazine act by upregulate or downregulate genes found to be downregulated or upregulated in HUVEC incubated with plasma from nonresponsive patients. Conclusion: Our novel findings suggest that plasma from nonresponsive and responsive patients evoke different responses in HUVEC, and might advance the pharmacogenomics research in pre-eclampsia.
Keywords: antihypertensive drugs; gene expression; human umbilical vein endothelial cells; hydralazine; nifedipine; pathway analysis; PCR array; pharmacogenomics; pre-eclampsia